VIDEO PLENARY 2: VID-HPB-01: An unusual appearance of space-occupying lesion in pancreas: Hydatid cyst - Choudhary, Narendra Singh (Endosc Ultrasound, 2017)
A 57-year-old male underwent ultrasound abdomen for nonspecific pain. The ultrasound abdomen showed a lesion in the body of pancreas. The patient was referred for endoscopic ultrasound (EUS) evaluation of a pancreatic lesion. EUS showed a 3.3 cm solid lesion in the body of pancreas with alternating thin hypoechoic and thick hyperechoic irregular layers giving it an appearance-like sulci and gyri of the brain. EUS-guided fine needle aspiration was done; the aspirate was positive for numerous hydatid scolices, thus confirming the diagnosis of pancreatic hydatid disease.